Relationship of Training Factors and Resilience with Injuries in Ski Mountaineers - Paula Etayo-Urtasun; Patxi León-Guereño; Iker Sáez; Arkaitz Castañeda-Babarro (MDPI AG, 2022)
Ski mountaineering is an increasingly popular sport with a relatively high risk of injury. Therefore, several studies have analyzed factors related to the likelihood of injury, including athlete characteristics, training, resilience and equipment. Thus, the aim of this study was to identify factors that may influence injury risk. A 15-minute online survey was sent to various ski mountaineering groups of different ages and levels. Both the Mann-Whitney U test and odds ratio analysis were performed in order to analyze the data. Results from 104 skiers showed that most injuries occurred in the lower extremities, especially in the knee (29.6%). The findings indicated that skiers who had suffered an injury performed in more competitions per year (p = 0.046), more ski mountaineering sessions per week (p = 0.022) and fewer core training sessions per week (0.029), although core training and competition were not statistically significant factors. Likewise, non-injured athletes had fewer pairs of skis (p = 0.019), which were also wider (p = 0.04). However, no difference was found for warm up and resilience between both groups (p = 0.275). In conclusion, it is important to implement preventive measures based on these factors, even if more research is needed.